187k views
2 votes
Use Gauss-Jordan elimination to solve the following linear system.

x – 6y – 3z = 4
–2x – 3z = –8
–2x + 2y – 3z = –14

2 Answers

0 votes

Answer:

(-2,-3,4)

Explanation:

User Yesim
by
6.2k points
7 votes

\begin{cases}x-6y-3z=4&(1)\\-2x-3z=-8&(2)\\-2x+2y-3z=-14&(3)\end{cases}

First eliminate
y by adding
(1) to three times
(3). This gives


(x-6y-3z)+3(-2x+2y-3z)=4+3(-14)\iff -5x-12z=-38

This reduces the system of one of two equations and two unknowns:


\begin{cases}-5x-12z=-38&(1)^*\\-2x-3z=-8&(2)^*\end{cases}

You can eliminate
z by subtracting
(1)^* and four times
(2)^* to get


(-5x-12z)-4(-2x-3z)=-38-4(-8)\iff3x=-6\implies x=-2

Back-substitute to find
z and
y. You should end up with
(x,y,z)=(-2,-3,4).
User Stephen Nguyen
by
6.8k points